The expanded judicial police authorities in drug crimes - Bellarou, Kamel (Journal of Human Sciences, 2020)
The inferential or preliminary investigations stage means those measures that the judicial police officers and their agents take in searching and investigating crimes to find out the perpetrators and how it occurred and attribute it to them. It is a stage prior to a public lawsuit and therefore it is a precedent for judicial work, and therefore it should be legitimate, because of that it should not be exercised by those who were not empowered by law to perform it, just as it is not permissible for judicial police officers and their agents exceeding the limits of the powers assigned to them and obliged to use legitimate means.and he initial investigation stage occupies a special importance that it is the stage on which all phases of the public.